INNOVATION OF PASSPORT SERVICES IN INDONESIA: A STUDY OF ACCELERATED PASSPORT SERVICES IN CLASS I IMMIGRATION OFFICES, ESPECIALLY TPI SOEKARNO HATTA - Laxmi, Devi Bethari; Nurkumalawati, Intan; Mastur, Anida Sri Rahayu (Polteknik Imigrasi, 2023)
Good governance is an important principle that must be integrated into every institution that provides public services, including the Immigration office of Soekarno Hatta, Indonesia. One of the latest innovations introduced at this office is the passport expediting service. In implementation, there are several technical and operational obstacles that need to be improved. This research uses a descriptive approach by collecting primary data and secondary data. Data collection was carried out in the Office Area on the 4th Floor of the International Terminal 3 Parking Building at Soekarno Hatta International Airport for seven months. Data was collected through observation, interviews, and documentation, then analyzed using data reduction methods, data presentation, and drawing conclusions. The passport acceleration service at the Immigration office of Soekarno Hatta, Indonesia has been running well and implementing the principles of good governance. However, several obstacles still arise, including limited community participation, the problem of duplicating passports, and the need to improve facilities and infrastructure. The passport printing system is also a challenge, along with the limited number of officers in the Passport Acceleration Service Unit (UP3). The passport shortage service at the TPI Soekarno Hatta Special Class I Immigration Office has fulfilled most of the indicators of good governance principles. To improve service operations, steps are needed such as providing discussion space for the public and public service providers, providing information and education to passport applicants to reduce duplication, as well as improving facilities and infrastructure. Evaluation of needs in UP3 is also important to ensure suitability with field implementation.